METHODS OF USING OUTDOOR GAMES WITH ELEMENTS OF MARTIAL ARTS IN THE SELECTION AND EARLY ORIENTATION TO THE TYPES OF WRESTLING (Scientific journal of the Fergana State University, 2024)
This article describes the methodology for using action games with elements of unicorn in qualifying and early guidance for sports wrestling. Sports wrestling (judo, freestyle and Greco-Roman wrestling, belt wrestling, wrestling) are games that incorporate elements of technique into the sport.